2016
DOI: 10.1016/j.phrs.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a composite library of clinically used drugs and well-characterized pharmacological compounds for cystathionine β-synthase inhibition identifies benserazide as a drug potentially suitable for repurposing for the experimental therapy of colon cancer

Abstract: Cystathionine-β-synthase (CBS) has been recently identified as a drug target for several forms of cancer. Currently no potent and selective CBS inhibitors are available. Using a composite collection of 8871 clinically used drugs and well-annotated pharmacological compounds (including the LOPAC library, the FDA Approved Drug Library, the NIH Clinical Collection, the New Prestwick Chemical Library, the US Drug Collection, the International Drug Collection, the `Killer Plates' collection and a small custom collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(104 citation statements)
references
References 76 publications
4
100
0
Order By: Relevance
“…In particular in human colon cancer, the most significant upregulation in tumor tissue (compared to surrounding tissue) was noted in CBS, with a trend for increase for 3-MST [26]. Likewise, in many human colon cancer cell lines, CBS was found to be highly expressed, and genetic silencing or pharmacological inhibition of CBS exerted antitumor effects in vitro and in vivo [24][25][26][37][38][39][40][41] while forced expression of CBS into non-transformed human epithelial cells increased their growth in situ (but did not render them metastatic) [42]. In contrast, in the current, murine colon cancer cell line, CBS (mRNA or protein) was undetectable (and, accordingly, the CBS inhibitor AOAA was without significant biological effects), while 3-MST was highly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular in human colon cancer, the most significant upregulation in tumor tissue (compared to surrounding tissue) was noted in CBS, with a trend for increase for 3-MST [26]. Likewise, in many human colon cancer cell lines, CBS was found to be highly expressed, and genetic silencing or pharmacological inhibition of CBS exerted antitumor effects in vitro and in vivo [24][25][26][37][38][39][40][41] while forced expression of CBS into non-transformed human epithelial cells increased their growth in situ (but did not render them metastatic) [42]. In contrast, in the current, murine colon cancer cell line, CBS (mRNA or protein) was undetectable (and, accordingly, the CBS inhibitor AOAA was without significant biological effects), while 3-MST was highly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…When benserazide was tested against the other two H 2 S-producing enzymes, it was found to only weakly inhibit CSE and 3-MST activity (16% and 35% at 100 mM, respectively). Moreover, the major benserazide metabolite 2,3,4-trihydroxybenzylhydrazine also inhibited CBS activity (Druzhyna et al, 2016). By using in silico docking simulations, we proposed that the mechanism of action of benserazide results from binding in the active site of the enzyme and reacting with the PLP cofactor, leading to the formation of a Schiff base-like adduct with the formyl moiety of pyridoxal (Druzhyna et al, 2016).…”
Section: Pharmacological Inhibitors Of Cystathionine-b-synthasementioning
confidence: 99%
“…It should be noted, however, that NSC67078 appears to have several additional pharmacological targets in addition to CBS; moreover, in the fluorescent assay used to estimate its potency, it also inhibits the H 2 S H 2 S Donors and H 2 S Biosynthesis Inhibitors signal elicited by GYY4137, indicative of additional pharmacological actions beyond inhibition of the catalytic activity of CBS (e.g., H 2 S scavenging and potent inhibition of the b-catenin pathway (as discussed in Druzhyna et al, 2016). The most recently published effort to identify new CBS inhibitors through highthroughput screening used a natural compound library, yielding 11 hits with IC 50 below 20 mΜ.…”
Section: Pharmacological Inhibitors Of Cystathionine-b-synthasementioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have reported the identification of CBS inhibitors (39-44) but most of them were based on in vitro assays using a recombinant CBS enzyme as a drug target and led to the isolation of inhibitors with relatively low potency and limited selectivity, hence leading to the idea that CBS may be an undruggable enzyme. Therefore we oriented toward an in cellulo phenotype-based assay that would allow screening drugs that interfere with the phenotypical consequences of CBS overexpression and thereby that do not necessarily directly target the CBS enzyme.…”
Section: Resultsmentioning
confidence: 99%